2017
DOI: 10.1016/j.rehab.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of virtual reality to the diagnosis of spatial navigation disorders and to the study of the role of navigational aids: A systematic literature review

Abstract: Unlike pencil-and-paper tests, virtual reality is useful to assess large-scale navigation strategies in patients with brain injury or schizophrenia, or in the context of ageing and dementia. Better knowledge about both the impact of the different aids and the cognitive processes involved is essential for the use of aids in neurorehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
66
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 93 publications
3
66
0
13
Order By: Relevance
“…Past research comparing navigation in real and VR environments has generally found a good concordance in performance across both environments in the normal population [14][15][16][17][18][19], in younger and older age groups [20], in individuals with brain injury [21,22], in chronic stroke patients [23], and in patients with Mild Cognitive Impairment (MCI) or early AD [20,24], for reviews see [25,26]. However, this consistency seems to be modulated by the type of spatial navigation task: in [27], the authors show that performance in real life and virtual environments were similar for tasks such as landmark recognition or route distance estimate, but different for pointing to the beginning and endpoint of the route, or drawing a map of the route.…”
Section: Introductionmentioning
confidence: 99%
“…Past research comparing navigation in real and VR environments has generally found a good concordance in performance across both environments in the normal population [14][15][16][17][18][19], in younger and older age groups [20], in individuals with brain injury [21,22], in chronic stroke patients [23], and in patients with Mild Cognitive Impairment (MCI) or early AD [20,24], for reviews see [25,26]. However, this consistency seems to be modulated by the type of spatial navigation task: in [27], the authors show that performance in real life and virtual environments were similar for tasks such as landmark recognition or route distance estimate, but different for pointing to the beginning and endpoint of the route, or drawing a map of the route.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted on navigation has found strong correlations between real-world and virtual navigation (Richardson et al, 1999;Gaunet et al, 2001;Claessen et al, 2016) which has led to virtual environments being used to investigate spatial cognition in simulated real environments. This has been applied to particular cases such as Alzheimer's, people with brain injury or orientation activities in elderly people (Foreman et al, 2005;Plancher et al, 2012;Cogné et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ориентация в пространстве -это сложная многокомпонентная функция, обеспечивающая возможность определения своего местонахождения и траектории передвижения относительно других объектов внешнего мира [1][2][3]. Под «топографической дезориентацией» понимают нарушение способности больного узнавать местность и ее ориентиры, распознавать свое положение в пространстве, находить ранее знакомые маршруты и запоминать новые, использовать карту для ориентации [4][5][6][7][8][9].…”
unclassified
“…Широкое распространение получили диагностические тесты для оценки возможностей пространственной навигации в виртуальном пространстве [8]. В частности, V. Bellassen и соавт.…”
unclassified
See 1 more Smart Citation